The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1007/s11548-014-1084-y
|View full text |Cite
|
Sign up to set email alerts
|

Statistical atlas-based morphological variation analysis of the asian humerus: Towards consistent allometric implant positioning

Abstract: Morphologic analysis based on statistical atlases is novel and useful to characterize the Asian humerus. The humerus demonstrates gender-specific morphology. This unique approach provides information that is useful to the clinician and biomedical engineer, not only in the modification of current or design of future humeral implants, but also in the precise dynamic positioning of Asian-specific humeral implants to Asian patients. Our findings support the need for further development of humeral implants, curvili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Linear distances omit information about relationships involving the shape of the object. Lately, statistical bone atlases have been used to investigate the bilateral asymmetry of the human skeleton (e.g., Fatah et al, ) or to develop the field of biomedical engineering (e.g., Wu et al, ). However, recent advances in three‐dimensional reconstruction and improvements in geometric morphometrics analyses (GM) have enabled testing of more sophisticated biological hypotheses (e.g., Bejdová et al, ; Bigoni et al, ; Frelat et al, ; Harcourt‐Smith et al, ; Kubicka et al, ; Velemínská et al, ) and enabled the illustration of differences in shape between objects (Mitteroecker and Gunz, ; Zeldith et al, ).…”
mentioning
confidence: 99%
“…Linear distances omit information about relationships involving the shape of the object. Lately, statistical bone atlases have been used to investigate the bilateral asymmetry of the human skeleton (e.g., Fatah et al, ) or to develop the field of biomedical engineering (e.g., Wu et al, ). However, recent advances in three‐dimensional reconstruction and improvements in geometric morphometrics analyses (GM) have enabled testing of more sophisticated biological hypotheses (e.g., Bejdová et al, ; Bigoni et al, ; Frelat et al, ; Harcourt‐Smith et al, ; Kubicka et al, ; Velemínská et al, ) and enabled the illustration of differences in shape between objects (Mitteroecker and Gunz, ; Zeldith et al, ).…”
mentioning
confidence: 99%
“…Accordingly, it is necessary to consider the sex difference in the usable bone volume. Regarding bones with a sex difference, Wu et al 31) discovered that the length and width of the humerus were larger in males, and Zubin et al 32) reported that the length, width, and thickness of the clavicle were larger in males.…”
Section: Sex Differencesmentioning
confidence: 99%
“…In order to cater to the Asian patients, a statistical atlas [6] has to be worked out first. This paper gives a review of the progress of the construction of the Asian atlas and subsequently the approach of creating the preliminary implant for Asians, which are significant for minimally invasive procedures [7,8,9,10,11] in general and for robotic surgeries [12,13,14,15,16,17,18]. To summarize, the primary contributions of this paper include a new proposed methodology for the obtainment of curvature from the newly created Asian statistical atlas.…”
Section: Introductionmentioning
confidence: 99%